Digitalize Training Administration Application to Support Aviation Polytechnic towards Smart Vocational Training Centre - Ayub Wimatra; Hadi Prayitno; Sukarwoto; Ahnis Zulkarnain (International Journal of Science and Society, 2023)
This research aims to develop a "Digitalize Training Administration" application to support Medan Aviation Polytechnic in realizing the vision of "Smart Vocational Training Centre". This application is designed to replace the conventional education administration system with an integrated system that is easy to use. The research method used is a qualitative approach with a case study as the research design. Data were collected through observation, interview, and documentation. As part of the Medan Aviation Polytechnic, the Aircraft Maintenance Technology Study Program (TPPU) plays an important role in vocational education and has been certified as an Approved Aircraft Maintenance Training Organization (AMTO) by DKPPU. However, the management of AMTO currently faces various challenges that need to be addressed, including issues in administration and accessibility. The implementation of this application has proven to be able to improve the quality of AMTO management in a systematic and organized manner, achieving the expected efficiency. This application simplifies the management of schedules, registration, and monitoring and evaluation of education administration. It is hoped that this application can assist Medan Aviation Polytechnic in improving the efficiency and effectiveness of education implementation, and encourage the formation of a modern and innovative "Smart Vocational Training Centre".